Adaptation and validation of the Instrumental Expressive Social Support Scale in Portuguese older individuals - Lígia Lima; Célia Santos; Celeste Bastos; Marina Guerra; Maria Manuela Martins; Patrício Costa (Universidade de São Paulo, 2018)
Objective to adapt and validate the Instrumental Expressive Social Support Scale (IESS) in a sample of older people. Method methodological study. The sample of 964 community-dwelling older people was randomly divided into two groups. The first group was used as a calibration sample to study the number of factors underlying social support through Principal Axis Factoring, and the second group as a validation sample to test the "best fit" model through Confirmatory Factor Analysis. Results exploratory Factor Analysis suggested a three-factor solution, which was confirmed by Confirmatory Factor Analysis. The factors were similar to those in the pre-existing dimensions of the original instrument and were named as Sense of control (α = 0.900), Financial support (α = 0.802), Familiar and socio-affective support (α = 0.778). Confirmatory Factor Analysis showed acceptable fit. The model's goodness-of-fit indexes were satisfactory (χ2/df = 5.418; CFI = 0.903; NFI = 0.884; RMSEA = 0.098). The convergent validity was supported by associations between social support and medication adherence and positive affect. The discriminant validity was evidenced by association with negative affect. The reliability analysis showed high values of internal consistency. Conclusion the instrument proved to be a valid measure for the assessment of social support in older people.